PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP PROFITABILITAS (ROE) PADA BANK UMUM SYARIAH DI INDONESIA PERIODE 2010-2015 - LIDIA DESIANA; MAWARDI MAWARDI; SELLYA GUSTIANA (I-Finance Journal, 2016)
GCG (Good Corporate Governance) is an important thing in company. The company who already proved this systems will tend to have a good governance as well.The data used in this research is secondary data which are the financial statements of the islamic common bank In Indonesia periods 2010-2015. The data sources in this research were obtained through annual reports. The population used in this research took five samples of islamic banks in indonesia with the sampling technique by purposive sampling.This research using simple linear regression method. Based on the results of hypothesis testing shows that good corporate governance variable to profitability variable has positive effect and the results of the analysis described that GCG has effect significantly to profitability with thitung = 2,567 (t hitung > t tabel). The meaning is GCG is very influence to ROE.Keyword : good corporate governance, ROE